2004
DOI: 10.1161/01.atv.0000112930.40564.89
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Apoptosis Signal-Regulating Kinase-1 on Angiotensin II-Induced Monocyte Chemoattractant Protein-1 Expression

Abstract: Objective-Monocyte chemoattractant protein 1 (MCP-1) could contribute to enhanced leukocyte recruitment and activation resulting in chronic tissue damage. However, little is known about the molecular mechanisms of cardiac MCP-1 expression. To elucidate these molecular mechanisms, angiotensin II-induced expression of MCP-1 was examined in cultured rat neonatal ventricular cardiomyocytes and fibroblasts by adenovirus gene transfer. Methods and Results-MCP-1 mRNA increased 3.6-fold in cardiac fibroblasts at 3 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…NF-κB is a ubiquitous rapid response transcription factor that modulates the expression of various cytokine and adhesion molecules. Activation of NF-κB up-regulates the expression of proinflammatory genes, such as vascular cell adhesion molecule 1 (VCAM-1) and monocyte chemoattractant protein 1 (MCP-1), that play pivotal roles in inflammation after ischemia [7,8]. These findings suggest that intervention with exogenous anti-oxidants may attenuate myocardial damage by inhibiting cardiomyocyte apoptosis and blunting the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is a ubiquitous rapid response transcription factor that modulates the expression of various cytokine and adhesion molecules. Activation of NF-κB up-regulates the expression of proinflammatory genes, such as vascular cell adhesion molecule 1 (VCAM-1) and monocyte chemoattractant protein 1 (MCP-1), that play pivotal roles in inflammation after ischemia [7,8]. These findings suggest that intervention with exogenous anti-oxidants may attenuate myocardial damage by inhibiting cardiomyocyte apoptosis and blunting the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ang II stimulates MCP-1 production from various cells including mononuclear cells, cardiovascular cells, preadipocytes, and adipocytes (Funakoshi et al 2001, Omura et al 2004, Tsuchiya et al 2006. In our Figure 4 Translocation of NF-kB p65 from cytosol to nucleus induced by Ang II and/or TNF-a.…”
Section: Discussionmentioning
confidence: 50%
“…Such inflammatory cytokines as TNF-a and angiotensin II (Ang II) are molecules reported to induce MCP-1 gene expression (Funakoshi et al 2001, Fain et al 2004, Omura et al 2004. The renin-angiotensin system (RAS) has been shown to be another important pathway in the pathogenesis of metabolic syndrome, especially in hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, antioxidants such as thioredoxin, a physiological inhibitor of ASK-1, inhibit cytokine-and stress-induced apoptosis (3)(4)(5)(6). Cardiac myocyte hypertrophy, a characteristic of cardiac remodeling, requires activation of ASK-1 and nuclear factor κB (16). Thus, ASK-1 is considered essential for a variety of physiological functions, such as apoptosis (7).…”
Section: Discussionmentioning
confidence: 99%